Home in John McGahern's Prose - Sekaninová, Jana (Univerzita Pardubice, 2025)
This bachelor thesis examines the depiction of certain aspects of home in selected literary works by John McGahern. Drawing on the concepts from humanistic geography, the thesis defines key terms that form the atmosphere of home, namely, love, safety, and belonging. Through the analysis of the selected literary works, the thesis examines the impact of the absence of these aspects on the characters and their perception of home with emphasis on feelings of alienation and loss of home.
Domov v próze Johna McGaherna
Keywords: láska; bezpečí; pocit sounáležitosti; ztráta domova; love; safety; belonging; home; loss of home